Math, asked by Arpit9889, 8 months ago

please explain and solve
don't spam​

Attachments:

Answers

Answered by biligiri
0

Step-by-step explanation:

let x = y², then the equation reduces to,

y² - 2y - 6 = 0

a = 1, b = -2 and c = -6

y = [- b ± √(b² - 4ac)] / 2a

y = [-(-2) ±√{(-2)² - 4×1×(-6)}] / 2

y = [2 ± √(4 + 24)] / 2

y = (2 ± √28)/2

y = (2 + √28) /2 and y = (2 - √28) / 2

therefore y² = x = [ (2 +√28)/2]² and x = [ (2 -√28)/2]²

x = (4 + 28 + 4√28)/4 and x = (4 + 28 - 4√28)/4

x = (32 + 4√28) / 4. and x = (32 - 4√28) / 4

x = 8 + √28 and x = 8 - √28

Similar questions